Analisis Pengaruh Kebijakan Moneter, Kebijakan Fiskal, dan Penyaluran Kredit Terhadap Pertumbuhan Ekonomi di Provinsi Jawa Timur Tahun 2006-2016 - Muara Nangarumba (Jurnal Ekonomi dan Studi Pembangunan, 2016)
Economic growth over the years is believed to be an indicator that can detect how the economics activity in an area. regardless of the debate between development and economic growth, there is no doubt that economic growth remains keep economic role in the region. In keeping with the economic growth in order to remain on a positive trend, the necessary interaction between monetary and fiscal policy. However, both the policy has a different authority. If monetary policy is more controlled by the central government, fiscal policy with fiscal decentralization has two elements of the center and affluent. The interaction between monetary and fiscal policy is believed to give good influence for economic growth, and therefore in this study it was found that through proper credit will be able to have positive influence on economic growth. In addition, this study found the sectors that can be targeted increase in lending growth to the economy, especially the Province of East Java which is the object of research in this study, is expected to increase. These sectors are the Services Sector, Industrial Sector, Agriculture, Trade Sector, and the Construction Sector.Keywords: Economic Growth, OLS Regression, Path Analysis, Fiscal Policy, Monetary Policy, CreditJEL Classification: E01, E52, E62